2018
DOI: 10.1016/j.gore.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Extragastrointestinal stromal tumors of the pelvic cavity and the vagina: Two case reports and review of the literature

Abstract: Gastrointestinal stromal tumors (GISTs) are rare tumors of gastrointestinal (GI) tract with mesenchymal cell origin. Extragastrointestinal stromal tumors (EGISTs) are unusual tumors that exhibit the same immunohistochemical and genetic abnormalities as GISTs and most commonly affect the omentum and mesentery. EGISTs of the pelvis and the female reproductive system are exceedingly rare and a frequent diagnostic pitfall. In this report, we present two cases of EGISTs along with a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…The most common presenting symptom is awareness of a mass in the vagina. Vaginal EGISTs can be asymptomatic or may have primary symptoms of bladder outlet obstruction or vaginal bleeding ( Ceballos et al, 2004 , Hanayneh et al, 2018 , Weppler and Gaertner, 2005 ). Severe constipation and rectal mucosal involvement have also been reported to be associated with GISTs involving the rectovaginal septum ( Nasu et al, 2004 , Zhang et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common presenting symptom is awareness of a mass in the vagina. Vaginal EGISTs can be asymptomatic or may have primary symptoms of bladder outlet obstruction or vaginal bleeding ( Ceballos et al, 2004 , Hanayneh et al, 2018 , Weppler and Gaertner, 2005 ). Severe constipation and rectal mucosal involvement have also been reported to be associated with GISTs involving the rectovaginal septum ( Nasu et al, 2004 , Zhang et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Routine follow-up gynecologic examination is warranted ( Lam et al, 2006 ). Targeted therapy such as imatinib has been administered postoperatively in some previously reported cases ( Hanayneh et al, 2018 ). A randomized controlled trial showed that adjuvant therapy was able to prolong recurrence-free survival, with no recurrence found at 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was the first case of EGIST originating from the pericardium. Reports of EGIST presenting in the kidney, adrenal gland, inferior vena cava, vagina, and scrotum have been found [9][10][11][12][13]. Diagnosis can often be delayed due to small tumor size and lack of clinical symptoms in the tumor's early stages [1,8].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms and signs may include enlarging abdominal mass (ranging 2–32 cm, with most >10 cm), swelling, bloating and even acute abdomen ( Fletcher et al, 2002 ). Acute severe abdominal pain can be due to tumor rupture with subsequent bleeding, GI obstruction, or pain may mimic appendicitis ( Hanayneh et al, 2018 ). Initial diagnosis of EGIST is challenging when based on variable presentations and imaging alone ( Weppler and Gaertner, 2005 ).…”
Section: Introductionmentioning
confidence: 99%